Praktikum Sabun Cair dengan Ekstrak Bunga Sepatu: Mengembangkan Pemecahan Masalah Mahasiswa Kimia Melalui Kimia Terapan - Ahmadi, Ahmadi; Maripa, Baiq Risni (Indonesian Journal of STEM Education, 2022)
Problem-solving skills are an essential competency that chemistry education students must master as future educators. This study aims to analyze the effectiveness of a laboratory experiment on the formulation of liquid soap enriched with hibiscus flower extract (Hibiscus rosa-sinensis L.) in developing students’ problem-solving skills. The research design employed a pre-experimental approach with a one-group pretest-posttest design involving 15 fifth-semester chemistry education students at Mandalika University of Education. The learning intervention was designed based on contextual problems through six stages: orientation to formulation problems, extraction of bioactive components from hibiscus flowers, design of liquid soap formulas, implementation of manufacturing procedures, testing of product quality parameters, and reflective evaluation based on empirical data. The measurement instrument consisted of a structured essay test that assessed six problem-solving indicators: problem identification, conceptual analysis, solution planning, implementation strategies, data interpretation, and critical evaluation. Data analysis utilized the Shapiro-Wilk normality test, paired t-test, normalized gain, and Cohen’s d effect size. The results showed a significant increase in problem-solving scores from a mean of 50.4 (SD=10.2) to 85.6 (SD=7.8), with a t-value (14)=4.26, p<0.001. An N-gain value of 0.71 indicates a high category, with an effect size of d=1.10 indicating a large practical impact. An applied chemistry context based on household products has proven effective in bridging the gap between theoretical knowledge and real-world applications in chemistry education.